The aerosmurf : a Smurfs graphic novel - Peyo (Peyo. Smurfs graphic novel, 2013)
In "The Aerosmurf," the Flying Smurf must use his new flying machine to rescue Smurfette from Gargamel. In "The Masked Smurf," when Smurfs start getting hit in the face with cream pies, every Smurf wants to solve the mystery of the masked Smurf. In "The Firesmurfs," there's a heat wave and a fire breaks out in Smurf Village--call in the Firesmurfs! In "Gluttony and the Smurfs," has Gargamel finally found the one thing Smurfs cannot resist? In "The Smurf and His Dragon," when lonely Timid Smurf befriends Grumpf the Dragon, has he unknownly placed all the Smurfs in danger? Finally in "Jokey Smurf's Pranks," how long can the Smurfs put up with Jokey's pranks, and what happens when Jokey discovers he can't quit pranking?